Endocrine and Genetic Mechanisms of the Influence of Subclinical Thyroid Dysfunction on Women’s Reproductive Health (Texas Journal of Medical Science, 2026)
Subclinical thyroid dysfunction is one of the most common endocrine disorders among women of reproductive age and represents an important medical and social problem due to its impact on fertility, menstrual function, pregnancy outcomes, and hormonal balance. Subclinical hypothyroidism and subclinical hyperthyroidism are characterized by altered thyroid-stimulating hormone levels with normal circulating thyroid hormone concentrations. Despite the absence of pronounced clinical manifestations, these conditions may significantly affect reproductive health through complex endocrine and genetic mechanisms. Thyroid hormones regulate ovarian function, folliculogenesis, ovulation, implantation, and placental development. Disturbances in thyroid homeostasis can lead to menstrual irregularities, infertility, miscarriage, polycystic ovary syndrome, and adverse obstetric outcomes. In recent years, increasing attention has been paid to the genetic and molecular mechanisms underlying the relationship between thyroid dysfunction and reproductive disorders. Genetic polymorphisms involving thyroid hormone receptors, deiodinases, autoimmune susceptibility genes, and reproductive hormone receptors may contribute to impaired fertility and hormonal imbalance in affected women. This article reviews current scientific evidence regarding the endocrine and genetic pathways linking subclinical thyroid dysfunction with female reproductive health and highlights the importance of early diagnosis and personalized therapeutic strategies.